2017
DOI: 10.17576/jkmjc-2017-3302-02
|View full text |Cite
|
Sign up to set email alerts
|

Media Agenda and Public Agenda: A Study of Issues during the 13th General Election

Abstract: Media might play an important role in public's voting decision. Even so, it is unknown whether the media agenda counterpart public agenda with regard to the level of importance of the issues covered in the media. This study examined the issues of concern by the Malaysian mainstream newspapers, as well as the issues of concern by the public during the 13th General Election (GE 13). In particular, this study explored the relationship between media and public agenda; as well as the relationship between Malay lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…[29] states that "Mobile technology and social media exert a substantial impact on our society and daily lives". A similar view is expressed by [30], that social media and the internet have become the main media which substitute the national newspapers, "Mass media are said to report issues that are related to the agenda and have set to influence the public's opinion." Furthermore, [9] explains about the communication in the family and public space, "connection of private familial spheres to larger public discourses and structures; and inherent openness to critique, resistance, and transformation of the status quo".…”
Section: Figure 3 Communication Of Three Education Centermentioning
confidence: 80%
“…[29] states that "Mobile technology and social media exert a substantial impact on our society and daily lives". A similar view is expressed by [30], that social media and the internet have become the main media which substitute the national newspapers, "Mass media are said to report issues that are related to the agenda and have set to influence the public's opinion." Furthermore, [9] explains about the communication in the family and public space, "connection of private familial spheres to larger public discourses and structures; and inherent openness to critique, resistance, and transformation of the status quo".…”
Section: Figure 3 Communication Of Three Education Centermentioning
confidence: 80%
“…While there have been many studies on the impact of Internet and social media on Malaysian politics (Idid, 2017;Manaf, Taibi & Manan, 2017) much of the focus has been on Facebook (Zanuddin et al, 2017;Lee, 2017). This is expected, as Facebook is the most popular and dominant social networking site in the world.…”
Section: The 14th Malaysian General Electionmentioning
confidence: 99%
“…Even before the historic 14 th General Election, many prominent Malaysian politicians were already engaging with the electorate via Facebook. Lee (2017) studied the presence of Malaysian politicians on Facebook by exploring the number of Facebook followers, Malaysian political parties and several prominent Malaysian politicians . His study found that the use of Facebook for politics is more intensive at the politicians' individual level than at the political party and political coalition level.…”
Section: Introductionmentioning
confidence: 99%
“…His study found that the use of Facebook for politics is more intensive at the politicians' individual level than at the political party and political coalition level. Lee (2017) further discovered that the level of social media presence, when measured by the number of followers, was uneven within coalitions and parties. For example, within Barisan Nasional (BN) and UMNO, the then Prime Minister Najib Razak has invested a lot to maintain a significant social media presence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation